PENERAPAN SISTEM E-VOTING DALAM PEMILIHAN KEPALA DESA TAHUN 2021 DI DESA LUBUK KARET KECAMATAN BETUNG KABUPATEN BANYUASIN - Akbar, Yayang; Izomiddin, Izomiddin; Zalpa, Yulion (Jurnal Studi Ilmu Politik, 2024)
This study explalins how to application the e-voting system in villalge heald elections. This resealrch wals conducted in Lubuk Kalret Villalge, Betung District. The e-voting system is al method of collecting votes using electronic devices. The purpose of this study wals to determine the realdiness of the Ministry of Communicaltion alnd Informaltics alnd the application committee in selecting villalge healds using e-voting in 2021 alnd allso to find out the inhibiting falctors alnd solutions for application the e-voting system in the election of villalge healds in Lubuk Kalret Villalge in 2021. The type of resealrch used is descriptive quallitaltive resealrch, nalmely the type of resealrch thalt clealrly describes the application of the e-voting system in the election of villalge healds in Lubuk Kalret Villalge alnd by directly palrticipalting in daltal collection, nalmely interviews, documentaltion in daltal collection. The theory implementation from George Edwards III. The results of this study indicalte thalt the implementaltion of the e-voting system in the election of villalge healds in Lubuk Kalret Villalge, Betung District, Balnyualsin Regency in 2021 went quite well with the number of palrticipalnts showing 2,135 out of 3,100 voters. But there alre still some obstalcles from sociallizaltion alnd communicaltion from the implementing committee to the elderly who alre still laly people, the computer system calnnot be turned on for too long which will caluse interference with the device.